Sustainability Accounting in Entrepreneurial Perspective: Pentuple Bottom Line Concepts - Fauziah, Dien Ajeng; Khoir, Fatihul; Sa’adah, Ummi; Prastyo, Dimas Hadi; Hermanto, Bambang Agoes; Lestari, L. Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sustainability accounting, particularly from an entrepreneurial perspective, is increasingly recognized as a critical framework for measuring and enhancing business performance. The Pentuple Bottom Line (PBL) paradigm expands upon traditional accounting frameworks by incorporating five dimensions: people, planet, profit, phenotechnology, and prophet. This holistic approach emphasizes not only financial success but also ethical responsibilities and the broader impact of business activities on society and the environment. Embracing the Pentuple Bottom Line paradigm not only supports sustainable business practices but also aligns entrepreneurial ventures with broader societal goals. By prioritizing ethical considerations alongside traditional profit metrics, businesses can contribute to a more sustainable future while achieving long-term success.